Latihan Sepeda Statis Meningkatkan Peak Expiratory Flow (PEF) dan Mengurangi Frekuensi Kekambuhan pada Penderita Asma - Maulani, Maulani (IJNP (Indonesian Journal of Nursing Practices), 2014)
Background. Asthma is an infl ammatory airways disease characterized by widespread narrowing of the airways, which is caused by bronchospasm, mucosal edema, and mucus hypersecretion are strong relapse, recurrent and reversible. Value of peak expiratory fl ow (PEF) is one indication of airway obstruction. Asthma management in addition to pharmacotherapy also do sports like gymnastics with asthma and exercise bike. Exercise statis bike improves cardiorespiratory work include increased heart rate. Exercise statis bike can gradually increase the intensity of peak expiratory fl ow and reduce the frequency of recurrence.Method. The aim of research was to assess the eff ectiveness of the exercise bike to increase Peak expiratory fl ow (PEF) and the frequency of recurrence than gymnastics asthma. This study used a quasi- experimental method with pretest- posttest design with control group. Number of respondents by 28 people. PEF value measurements used a peak flow meter Philips respironics, and note the frequency of recurrence with observation record sheet. Measured before exercise and after axercise.Result. The results of this research showed a signifi cance value (P= 0.000) of PEF, the frequency of recurrence (p=0.001) (p0.05) significantly different before and after the exercise bike. Unpaired t-test significance value of PEF (p=0359), Frequency of recurrence (p=0.050) (p 0.05). There were no significant differences after exercise between the treatment and comparison groups.Conclusions. Exercise statis bike can increase the value of PEF and reduce the frequency of recurrence in patients with asthma.Keywords: Exercise Statis Bike, Exercise Asthma Gymnastics, Peak Expiratory Flow (PEF), The Frequency Of Relapses, Asthma.